The Chronotope of City of Love: The Image of Kaunas in Lithuanian Culture - Petrulionytė, Justina (Respectus Philologicus, 2015)
This article discusses the image of Kaunas as a city of love, which is noticeable in different narratives: novels The Novel of Kaunas (1973) by Alfonsas Bieliauskas and Tūla (1993) by Jurgis Kunčinas, the social advertisement “Wherever I Am: Kaunas Is My Hometown” by Monika Vilčinskienė (2008) and the representative Kaunas video “Kaunas Is Sharing Love” by the Studio of Kaunas Cinema (2013). The concept of “narrative as a socially symbolic act” (Fredric Jameson) and the concept of “chronotope” (Mikhail Bakhtin) help to analyse emerging images of the city. The investigation reveals that all the narratives represent: 1) love for Kaunas, 2) a city where people are (happily or unhappily) in love, 3) personified city, which is in love. This shows the mark of love which is significant in the whole narrative of Kaunas. However, different modes of art production propose different mirages of this city. The chronotope of unhappy love is noticeable in the novels representing soviet Kaunas, while the chronotope of idyllic city is very bright in non-literary narratives representing current Kaunas.